The Economic Role of the Audit in Free and Regulated Markets (Book). - Winkle, Gary M.; Meyer, Philip E. (The Accounting Review, 1982)
Reviews the book "The Economic Role of the Audit in Free and Regulated Markets," by Wanda A. Wallace.